First report of the genus Umbelligerus Deitz, 1975 (Hemiptera: Membracidae: Stegaspidinae) for Colombia - Torres-Domínguez, Diana Marcela; Posso-Gómez, Carmen Elisa; González-Mozo, Laura Catalina; González-Obando, Ranulfo (Instituto de Ecología, A.C., 2019)
The genus Umbelligerus is reported for the first time in Colombia from the review of a male specimen found in the department of Amazonas. This specimen was deposited in the Museo de Entomología de la Universidad del Valle. A map of the known geographical distribution and photographs of the Umbelligerus peruviensis are included.